Scale‐dependent changes in tree diversity over more than a century in eastern Canada: Landscape diversification and regional homogenization. (16th August 2020) - Danneyrolles, Victor; Vellend, Mark; Dupuis, Sébastien; Boucher, Yan; Laflamme, Jason; Bergeron, Yves; Fortin, Gabriel; Leroyer, Marie; de Römer, André; Terrail, Raphaële; Arseneault, Dominique
Abstract: A better understanding of how disturbance impacts tree diversity at different scales is essential for our ability to conserve and manage forest ecosystems in the context of global changes. Here we test the impacts of land use‐related disturbances on tree diversity since the 19th century across a broad region (>150, 000 km 2 ) of northern temperate forests in eastern Canada. We used a large and unique dataset of early land surveys conducted during the 19th century (>130, 000 species lists), along with modern forest inventories (>80, 000 plots), to analyse long‐term changes in taxonomic and functional tree diversity at several scales (grid cell resolutions ranging from 12.5 to 1, 600 km 2 ; we refer to one grid cell as a 'landscape'). Our results show that land use‐related disturbances have led simultaneously to (a) increased diversity within landscapes and a (b) homogenization at the regional scale (i.e. decreased composition dissimilarity among landscapes). These trends were found for both taxonomic diversity and functional diversity, with temporal changes more pronounced for taxonomic than functional diversity. We also found an increase over time in the strength of correlations between environmental variables and diversity both within and among landscapes. Synthesis . Our results support the idea that human‐induced impacts on biodiversity are strongly scale‐dependent and not necessarily associated with biodiversity loss. This highlights possible ways that human‐driven changes in tree diversity might impact forest resistance and resilience to future global changes. Abstract : Our results show that land use‐related disturbances have led simultaneously to increased diversity within landscapes and a homogenization at the regional scale (i.e. decreased composition dissimilarity among landscapes). This highlights possible ways that human‐driven changes in tree diversity might impact forest resistance and resilience to future global changes.